2011
DOI: 10.1186/1476-511x-10-126
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a probiotic soy product on fecal microbiota and its association with cardiovascular risk factors in an animal model

Abstract: BackgroundPrevious work showed that daily ingestion of an aqueous soy extract fermented with Enterococcus faecium CRL 183 and Lactobacillus helveticus 416, supplemented or not with isoflavones, reduced the total cholesterol and non-HDL-cholesterol levels, increased the high-density lipoprotein (HDL) concentration and inhibited the raising of autoantibody against oxidized low-density lipoprotein (ox-LDL Ab) and the development of atherosclerotic lesions.ObjectiveThe aim of this study was to characterize the fec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 45 publications
1
57
1
3
Order By: Relevance
“…Cavallini et al also reported that Clostridium spp. was negatively correlated with total cholesterol in serum (28). Clostridium species increase the expression of regulatory T cells, which regulate the immune response in the large intestine, and may thus help to maintain the gut barrier function (29).…”
Section: Discussionmentioning
confidence: 99%
“…Cavallini et al also reported that Clostridium spp. was negatively correlated with total cholesterol in serum (28). Clostridium species increase the expression of regulatory T cells, which regulate the immune response in the large intestine, and may thus help to maintain the gut barrier function (29).…”
Section: Discussionmentioning
confidence: 99%
“…was obtained for the animals administered the E. faecium suspension. 44 Cavallini et al, 45 in contrast, performed another experiment, in which a probiotic soy product was administered to white rabbits and posterior analyses of microbiota were performed in vitro. In this case, the difference in bacterial populations obtained between fermented and unfermented products were more significant regarding with PPE, which was accompanied by a marked increase in the production of short chain fatty acids.…”
Section: Soy Productsmentioning
confidence: 99%
“…The advantages of fermented soy milk are that undesirable soybean oligosaccharides can be hydrolysed which provide nutritional components for probiotic and a large variety of peptides and amino acids are produced as well as active aglycon form of isoflavones [13]. An improved cholesterol profile was observed with daily intake of a probiotic soy product [14]. It seems possible that living probiotics and functional isoflavones cooperated in regulating lipid profile.…”
Section: Past and Presentmentioning
confidence: 99%